Reframing criminal profiling: a guide for integrated practice. Issue 5 (3rd September 2021) - Petherick, Wayne; Brooks, Nathan
Abstract : Profiling aims to identify the major personality and behavioural characteristics of offenders from their interactions in the crime. The discipline has undergone numerous changes and advances since its first modern use by the psychological/psychiatric community. The current paper reviews the different approaches to criminal profiling, exploring the reasoning and justification utilised across profiling practices. Profiling aims to assist criminal investigators; however, the variance in profiling approaches has contributed to inconsistency across the field, bringing the utility of profiling into question. To address the current areas of practice deficit in criminal profiling, a framework is proposed to promote integrated practice. The CRIME approach provides a framework (consisting of crime scene evaluations, relevancy of research, investigative or clinical opinions, methods of investigation, and evaluation) to promote structure and uniformity in profile development, aiming to assist in the reliability of the practice by providing an integrative framework for developing profiles.